Addressing the Limitations of Mathematics Teachers in the CLC Working Area of ​​KRI Tawau, Sabah, Malaysia: A Systematic Literature Review of Contextual Learning Videos Based on the REACT Strategy - Sunarsih; Kuswari Hernawati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study analyzes trends and developments of contextual learning videos and REACT strategies in mathematics learning through a Systematic Literature Review (SLR) of 168 papers published between 2020 and 2024. The SLR followed seven stages: (1) developing research questions, (2) building selection criteria, (3) developing search strategies, (4) selecting studies, (5) assessing quality, (6) synthesizing results, and (7) reporting findings. The analysis shows: (1) peak publications appeared in 2021; (2) Research and Development (R&D) methods dominate (33.9%), followed by quantitative (25%), qualitative (22%), and Classroom Action Research (19.1%); (3) no study integrates learning videos with contextual approaches and REACT strategies; (4) research subjects are mostly junior high school students (35.7%), then elementary (23.8%) and high school (16.1%); (5) problem-solving ability is the most studied mathematical skill, while connection and representation skills remain underexplored; (6) learning videos are the most widely used media (33.9%), but none combine them with the REACT strategy. This gap highlights the potential of developing contextual learning videos based on REACT. In contexts such as KRI Tawau, where resources and qualified mathematics teachers are limited, REACT-based contextual videos can serve as effective learning media—supporting or even substituting teachers in delivering materials. They also provide flexibility, as students can access, repeat, and use them anytime and anywhere. Thus, this study recommends future research and development of contextual learning videos integrating REACT strategies to enhance mathematics learning, particularly in areas with limited educational resources.